SELECTIVE DISSOLUTION OF MAGNETIC IRON OXIDES IN THE ACID-AMMONIUM OXALATE/FERROUS IRON EXTRACTION METHOD-I. SYNTHETIC SAMPLES - van Oorschot I.H.M.; Dekkers M.J. (My University, 2001)
In soil magnetism, the magnetic parameters alone are not always sufficient to distinguish the lithogenic from the pedogenic magnetic fractions. Sequential extraction techniques have therefore been incorporated into magnetic studies to constrain the environmental interpretation. Here we report on the dissolution behaviour of magnetite and maghemite in the acid-ammonium oxalate method to see whether the method is suitable for specific dissolution of magnetic minerals from soils and sediments. To prevent changes in the extraction mechanism during the experiments (see Appendix A), we used an adapted version of the acid-ammonium oxalate (AAO) method, in which Fe2+ is added to the extraction solution prior to the experiment [the AAO-Fe(II) method]. The procedure was divided into several 30 min extraction steps to check the dissolution progress. Synthetic samples containing a quartz matrix with 0.1 wt per cent of iron oxides were extracted with the AAO-Fe(II) method. The iron oxides consisted of either magnetite or maghemite with grain sizes of < 0.5 µm (fine grained or SD/PSD) and < 5 µm (coarse grained or MD/PSD), or a 1 : 1 mixture of both minerals. Because only magnetite and maghemite were studied, the changes in magnetic characteristics could be monitored after each extraction step by analysis of the bulk susceptibility and hysteresis parameters measured at room temperature. The AAO-Fe(II) method preferentially dissolved the smaller iron oxides from the samples. For samples containing iron oxides with coarse grain size there is a preference for dissolving maghemite rather than magnetite. Extractions of the samples containing mixtures of two different grain sizes or with different mineralogy show that the method preferentially dissolves the smaller grains before attacking the coarse grains in the sample.
Keywords: CHEMICAL EXTRACTION; ENVIRONMENTAL MAGNETISM; MAGHEMITE; MAGNETIC SUSCEPTIBILITY; MAGNETITE; ROCK MAGNETISM